(untitled) (Journal of Economic Research & Business Administration, 2020)
This is a comparative study of the effect of Profit After Tax (PAT) on Corporate Social Responsibility (CSR) expenditure in selected banks and manufacturing firms in Nigeria. A survey research design was used while a purposive sampling method was employed to select ten organizations. Specifically, a longitudinal survey research design was used for the study. This approach was chosen based on the purposes, nature and the variables that were examined. The data collected and analyzed through content analysis helped to reveal trends or changes in the subjects over the period of time under study. Secondary data were garnered from annual reports and accounts of selected companies for a decade, i.e. 2010 to 2019. Inferential statistics was used to analyse the data while the hypotheses were tested by correlation, ANOVA, and Pooled Ordinary Least Square (OLS). Result shows F = 35.37 and p = 0.043. Since pvalue is less 0.05, the fstatistics is significant. Hence, there is a significant difference between PAT and CSR expenditure in selected organizations. The study recommends that there should be an adjustment to the existing tax law in the country so that all expenditure on all form of CSR initiatives could be classified as tax deductible expenses.